2022
DOI: 10.1007/s00726-022-03177-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the predictive values of elevated serum l-homoarginine and dimethylarginines in preeclampsia

Abstract: Abstractl-homoarginine (hARG) is involved in nitric oxide biosynthesis, but its role and concentration in preeclampsia (PE) have not been fully revealed. The purpose of this study was to develop and validate a feasible clinical assay to quantify serum hARG, arginine (ARG), asymmetric (ADMA) and symmetric dimethylarginines (SDMA) levels by LC–MS/MS and investigate their differences at different stages of pregnancy with or without preeclampsia. Serum samples were collected from 84 pregnant women without complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Before the 20th pregnancy week and within the 20th - 28th pregnacy week, serum hArg concentration was found to be higher in mild preeclampsia than in pregnant women without preclampsia (about 8 vs. 5 μmol/l) as measured by LC-MS/MS [31 ▪▪ ] (Table 1). After the 28th pregnancy week, the serum hArg concentration was found be considerably lower in severe preeclampsia compared with mild preeclampsia [31 ▪▪ ]. This study showed that serum hArg and ADMA concentrations were similarly strong predictors of mild preeclampsia.…”
Section: Homoarginine In Pregnancy and Childhoodmentioning
confidence: 98%
“…Before the 20th pregnancy week and within the 20th - 28th pregnacy week, serum hArg concentration was found to be higher in mild preeclampsia than in pregnant women without preclampsia (about 8 vs. 5 μmol/l) as measured by LC-MS/MS [31 ▪▪ ] (Table 1). After the 28th pregnancy week, the serum hArg concentration was found be considerably lower in severe preeclampsia compared with mild preeclampsia [31 ▪▪ ]. This study showed that serum hArg and ADMA concentrations were similarly strong predictors of mild preeclampsia.…”
Section: Homoarginine In Pregnancy and Childhoodmentioning
confidence: 98%